THE CONCEPT OF DECISION MAKING IN LIFE (An Analytical Study of Narrative Verses in the Qur’an) - Alfi Ridho Muftih; Ziyad Ulhaq; Ade Naelul Huda (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Phenomena in the modern era show that adolescents are in a phase of crisis. Many adolescents are involved in deviant behavior and criminality; this condition is caused by the lack of attention and guidance from families and significant others. Families and significant others are obligated to educate adolescents, especially in matters of decision making. The method employed in this study is qualitative research based on library research. This study examines decision making verses related to the adolescent phase. There are five thematic narratives discussed: the story of Prophet Yusuf who was seduced by his master’s wife; the story of Prophet Ibrahim in his search for God leading to the destruction of idols; the story of the Companions of the Cave (Ashabul Kahfi) who took refuge in a cave; the story of the sacrifice of Prophet Ismail; and the story of Qabil who killed his brother. Based on these verses, interpretations by Muslim scholars are presented and subsequently analyzed using decision making theory. The results of this study indicate that the narratives mentioned above do not apply all methods within decision making theory; some of them prioritize intuition. This is because they are prophets and the friends of Allah, who possess intuition aligned with the divine light (nur Allah). In contrast, adolescents in the modern era are not in the same condition; they require education due to differing family and environmental backgrounds. Educating adolescents on the concept of decision making becomes a solution to minimize failures in making decisions that may have fatal consequences for their future. Keywords: Tafsir, Narrative Verses, Decision Making, Adolescents